Seroprevalence of influenza A H1N1 and seroconversion of mothers and infants induced by a single dose of monovalent vaccine - Anne Chao; Yhu-Chering Huang; Yao-Lung Chang; Tzu-Hao Wang; Shuenn-Dyh Chang; Ting-Shu Wu; Tsu-Lan Wu; An-Shine Chao (Elsevier, 2013)
Objective: To determine the prevalence of preexisting antibodies against the pandemic 2009 Influenza A (H1N1) virus in pregnant women and to evaluate the seroprotection of the mothers and infants by a single injection of monovalent vaccine during the pandemic. Materials and Methods: Seropositivity rate of H1N1 among the nonvaccinated were compared with the vaccinated women. A single dose of vaccine, either nonadjuvanted AdimFlu-S or MF59-adjuvanted vaccine, was injected to the voluntarily vaccinated group. Maternal and cord blood sera were collected to evaluate the antibody response of the H1N1 virus. Seropositivity was defined as a hemagglutination inhibition titer to H1N1 (A/Taiwan/126/09) ≥1:40. Results: A total of 210 healthy, singleton, pregnant women were enrolled between January 2010 and May 2010. Seropositivity (≥1:40) of maternal hemagglutination inhibition was significantly higher in the vaccinated group (78%) than the nonvaccinated group (9.5%); 41.6% (20/48) of seropositive titers were >1:80. In nine vaccinated cases resulting in negative serum titers (<1:40), the prevalence of negative titer in the women received AdimFlu-S (14.8%, 4/31) was lower (p = 0.025) than those received MF59-adjuvanted vaccine (50%, 5/10). Conclusions: Subclinical infection against H1N1 was low in Taiwanese pregnant women in the pandemic 2009. Seropositivity >75% could be achieved in the paired maternal and cord serum samples by a single injection of monovalent H1N1 vaccine.